Steenhouwtechnieken in de Onze-Lieve-Vrouwekerk in Breda. Detailanalyse van de bouw van het koor (Bulletin KNOB, 2020)
An extensive study in Belgium of the stone-cutting techniques on white Belgian limestone (Gobertange limestone (Brabant), Brussels limestone and limestone from Lede (Flanders)) has shown that the visible traces of the stone-cutting-work realized by the stone-mason changed twice during the first half of the 15th century: the first time between 1400 and 1420, and once again between 1430 and 1450.Based on archival information and dendrochronological dating work the construction of the choir of the Church of Our Lady in Breda could be dated between 1410 and 1450, thus making it an ideal study object for the ‘stone-cutting chronology’. By tracing the transitions of the stone-cutting techniques on all limestone masonry of the choir and linking them to other constructive anomalies, a very precise building chronology has been established with much more detail than was possible ever before.The two eastern crossing piers and the six columns of the choir have been identified as being the oldest elements of the sanctuary, erected around 1410. It has also been found that, once above the level of the capitals, the northern and southern sides did not show a synchronous development any longer: the three southern pier-arches were realized first, along with the choir columns, but the three northern ones were only built some time later. During this next step too the apse was erected all the way up, together with the corridor of the triforium in the square parts of the choir and with the southern aisle, the eastern wall of the southern transept and the triumph arch. Next, the choir’s clerestory was created together with the triforium’s tracery, which was fitted into the already constructed frame of the triforium, consisting of the masonry of the corridor and the interposed shafts of the projected vaulting. Around the same time, the erection of the old seigneurial chapel (the northern aisle of the choir) and of the adjoining eastern wall of the northern transept were started. The ribs and thus the vaults covering the three parts of the choir formed the final stage, to be dated around the middle of the 15th century or even somewhat later.Besides producing this precise order of building phases, this study also provided definite proof that the original apse was designed around 1425 with a single set of tall, elongated windows. At the beginning of the 16th century, along with the construction of the current ambulatory, the lower half of the original apse windows was altered into a series of pier-arches, while the upper half remained untouched. In this process, the moulded stones of these windows were removed at the level of the new attics over the ambulatory and the now useless parts of the mouldings were cut away (as was done with the preserved stones of the new arches). These recut stones were reused as arch bricks for the new pier-arches.All of the dendrochronologic datings of the roof constructions were taken into account in this study, but the analysis in detail of the complex construction of the three parts of this sanctuary, especially the answer to the age-old question about the exact shape of the original apse windows, and the very detailed description of their renovation, have only been possible thanks to the consistent analysis of the stone-cutting techniques.